1998
DOI: 10.1002/(sici)1096-8652(199802)57:2<124::aid-ajh6>3.0.co;2-y
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization and PCR diagnosis of Thailand deletion of α-globin gene cluster

Abstract: Thailand deletion of alpha-Thalassemia (thal) 1 involves the zeta2-, phi zeta1-, alpha2-, alpha1-, and theta1-globin genes. In Southeast Asians and Taiwanese, this mutation is the second most common long-segment deletion of two alpha-globin genes, after the Southeast Asian deletion. To define the Thailand deletion breakpoints, we used polymerase chain reaction (PCR) to amplify the normal-sequence DNA fragments across the breakpoints. The amplified products were sequenced directly or after cloning into pGem-3Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Apart from the requirement for an unusually high magnesium concentration in the reaction, the predicted primers worked perfectly and are therefore suitable for rapid diagnosis of DNA from subjects suspected of having the Filipino (Fil) total deletion. Ko et al (1998) have reported that the Thai deletion has a crossover at exactly the same point as we report here for the Fil deletion. Since they did not report how they characterized the Thai deletion, we can only assume they had misdiagnosed the hererozygotes used for characterization of the deletion and, in fact, were dealing with the Fil deletion.…”
Section: Discussionsupporting
confidence: 84%
“…Apart from the requirement for an unusually high magnesium concentration in the reaction, the predicted primers worked perfectly and are therefore suitable for rapid diagnosis of DNA from subjects suspected of having the Filipino (Fil) total deletion. Ko et al (1998) have reported that the Thai deletion has a crossover at exactly the same point as we report here for the Fil deletion. Since they did not report how they characterized the Thai deletion, we can only assume they had misdiagnosed the hererozygotes used for characterization of the deletion and, in fact, were dealing with the Fil deletion.…”
Section: Discussionsupporting
confidence: 84%
“…For PCR diagnosis of FIL, we used primers T83 (5b-ggtattctcaaggtgacactgagg-3b), T91 (5b-taaaccacccaatttttaaatgggc-3b), and T82 (5b-ataacctttatctgccacatgtagc-3b). The normal alleles have a 564-bp fragment with T91 and T83 and the affected alleles have a 560-bp fragment with T91 and T82 [11,12,19]. SBH using BglII and Asp718 double digestion and z-globin gene probe hybridization differentiated among SEA, rightward (-a 3.7 ) and leftward (-a 4.2 ) single a-globin gene deletion in one blot (Fig.…”
Section: Methodsmentioning
confidence: 94%
“…According to previous reports on the ethnic Chinese living in Taiwan, 3.5% are carriers of SEA, 0.17% of FIL, 0.6% of -a 3.7 , and 0.3% of -a 4.2 [12,15,19]. Significant differences in prevalence and molecular defects of a-thal also exist between the Philippines and Melanesia and regions in Southeast Asia [5,8,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequence analysis of each deletion breakpoint has now enabled PCR-based testing (22)(23)(24)(25)(26). Several techniques based on PCR amplification of normal and affected chromosomes (26 -28 ) have been developed to more rapidly identify globin gene mutations.…”
mentioning
confidence: 99%